Image of St. George as Dragon-Slayerr on the Seal M-8759 from the State Hermitage Museum Collection - Valerii Pavlovich Stepanenko (Античная древность и средние века, 2020)
This paper addresses the history of research of a Byzantine seal dating from the twelfth century and analyzes of its iconography. In 1884, Gustave Schlumberger first published an anonymous Byzantine seal from his private collection in the famous Byzantine Sigillography (p. 502). Between 1905 and 1910, Nikolai P. Likhachev acquired a part of G. Schlumberger’s collection. This anonymous seal attracted Likhachev’s special attention, as evidenced by the inventory card written by his hand that survived. When entering the State Hermitage Museum collection, this seal got the number M–8759. Later on, it became a subject of the research by Valentina S. Shandrovskaia. According to the legend on the reverse, the seal belonged to an official of unknown name with the rank of protospatharios ἐπὶ τοῦ Χρυσοτρικλίνου, who held the position of the domestikos tes ypourgeias (δομέστικος τῆς ὐπουργείας) at the Christ-loving despotes (i. e. emperor). The front side of the seal features St. George spearing a dragon. It has been noticed that the scene showing this saint performing the feat rarely occurs on the tenth-to-twelfth century Byzantine seals with similar iconography.